TRANSAKSI JUAL BELI MELALUI APLIKASI FACEBOOK DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI TRANSAKSI ELEKTRONIK - Syahputra, Moch. Rayhan Adityo; Sulistiyantoro, Hariyo (Gapenas Publisher, 2023)
deals that occur on Facebook Marketplace can be said to be legitimate. This is because the agreement fulfills the validity of the sale and purchase agreement, namely there is an agreement between the parties. So that agreements that occur on the Facebook Marketplace also have valid legal consequences with sales and purchase agreements in general. Article 1 number 2 of the Information and Electronic Transactions Law provides an understanding that electronic transactions are legal acts carried out using computers, computer networks and/or other electronic media. Based on Article 17 of the Information and Electronic Transactions Law, electronic transactions can be carried out in the public or private sphere. The Information and Electronic Transactions Law provides opportunities for the use of information technology by state officials, people, business entities or the public. The use of technology must be carried out well, wisely, responsibly, efficiently and effectively in order to obtain the greatest benefits for society. Article 20 of the Information and Electronic Transactions Law, Article 1458 of the Civil Code and Article 49 of the Government Regulations on the Implementation of Electronic Systems and Transactions are the basis for regulations regarding electronic buying and selling transactions via the Facebook Marketplace. Where in buying and selling transactions via Facebook Marketplace, an agreement between the seller and the buyer occurs when the seller sends an offer for goods and the buyer agrees to the offer